2020
DOI: 10.21831/cp.v39i3.31580
|View full text |Cite
|
Sign up to set email alerts
|

School Culture and Professional Development of School Teachers From Urban and Rural Areas in China

Abstract: Rural teacher recruitment and retention has become a common concern globally including in China. In order to understand the underlying reasons that cause rural teachers’ attrition, this study aims to explore the school culture and professional development of the teachers from urban and rural areas of China provinces, by examining three study objectives: teaching location and socio-demographic factor; challenges faced by rural teachers; and strategies to develop teaching professionalism in rural schools. A mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
0
11
0
2
Order By: Relevance
“…VOEs were essential to the success of the organizations in the village; hence, their management professionalism was crucial. Work professionalism would promote the growth of trust among stakeholders (Ling et al, 2020). It was also critical to avoid political issues and nepotism likely emerging in the village's institutional positions.…”
Section: Resultsmentioning
confidence: 99%
“…VOEs were essential to the success of the organizations in the village; hence, their management professionalism was crucial. Work professionalism would promote the growth of trust among stakeholders (Ling et al, 2020). It was also critical to avoid political issues and nepotism likely emerging in the village's institutional positions.…”
Section: Resultsmentioning
confidence: 99%
“…Discussion here includes the courage to express opinion, to appreciate others' opinion, and to establish close relationship between fellow citizens. Teachers play a very important role in creating the school citizens' habit (Ling et al, 2020). Therefore, teachers can create a discussion habit in solving problem in the class and to train the students to implement the principles contained in Pancasila as the part of nationalism internalization.…”
Section: Problem Solving Through Discussionmentioning
confidence: 99%
“…So, students are trained to attend discussion actively to learn how to be good citizens. The integration of Pancasila moral value into civic education is very effectively, one of which is through discussion (Ling et al, 2020). Discussion is conducted routinely every Monday to discuss the problem in the class to train the students to solve problem corresponding to Pancasila values.…”
Section: Problem Solving Through Discussionmentioning
confidence: 99%
“…As the working location is remote thus, many teachers are confronted with stress from family. A study pointed out that a research found that in China, male primary school teachers or unmarried teachers tend to be dissatisfied in rural schools [9], and other researchers found that male primary school teachers in rural schools find it challenging to get married and lack career development opportunities [10]. Rural educators also face many challenges during the teaching processes because they lack parent and education resources support.…”
Section: The Job Satisfaction Of Rural Teachersmentioning
confidence: 99%